Fairness as a constraint on trust in reciprocity: earned property rights in a reciprocal exchange experiment - Fahr, René; Irlenbusch, Bernd (Economics Letters)

Gibt es eine Nachfrage nach produktiver Freizeit - Fahr, Rene (Statistisches Bundesamt (Hrsg.), Spektrum Bundesstatistik)

The promise of workplace training for non-college-bound youth: Theory and evidence from German apprenticeship - Clark, Damon; Fahr, Rene (CEP Discussion Paper No. 528)

Transferability, mobility and youth training in Germany and Britain: A simple theoretical analysis - Clark, Damon; Fahr, Rene (KONJUNKTURPOLITIK-BERLIN-)

Occupational Mobility and Occupational Matching: Some Implications for Career Choice and Labor Market Policy - Fahr, Rene

A Comparative Analysis of Job Entry Methods in Japan, the US and Europe (Japanese) - Toshihiro, KODAMA; Yoshio, HIGUCHI; Masahiro, ABE; Fahr, Rene

Loafing or Learning? - Fahr, Rene (The Economics of Time Use)

Job and vacancy competition in empirical matching functions - Fahr, Rene; Sunde, Uwe (Labour Economics)

Loafing or learning?—the demand for informal education - Fahr, Rene (European Economic Review)

Spatial mobility and competition for jobs: Some theory and evidence for Western Germany - Fahr, René; Sunde, Uwe (Regional Science and Urban Economics)

Regional dependencies in job creation: an efficiency analysis for Western Germany - Fahr, Rene; Sunde, Uwe (Applied Economics)

The wage effects of social norms: evidence of deviations from peers' body-mass in Europe - Fahr, Rene

Immigration policy and the labor market: the German experience and lessons for Europe - Zimmermann, Klaus F; Bonin, Holger; Fahr, Rene; Hinte, Holger

On the inverse relationship between unemployment and absenteeism: evidence from natural experiments and worker heterogeneity - Fahr, Rene; Frick, Bernd

Identifying personality traits to enhance trust between organisations: An experimental approach - Fahr, Rene; Irlenbusch, Bernd (Managerial and Decision Economics)

Returns to company training--Evidence from a new approach using quasi experimental data - Fahr, Rene; Simons, Sabine

Did the Hartz Reforms speed-up the matching process? A macro-evaluation using empirical matching functions - Fahr, René; Sunde, Uwe (German economic review)

Gender differentials in skill use and skill formation in the aftermath of vocational training - Fahr, Rene; Sunde, Uwe (Applied Economics Letters)

Who follows the crowd—Groups or individuals? - Fahr, René; Irlenbusch, Bernd (Journal of Economic Behavior & Organization)

Job design and job satisfaction—empirical evidence for Germany? - Fahr, René (management revue)

When the early bird catches the worm: The impact of training in retail - Hinerasky, Christiane; Fahr, Rene

Individual determinants of work attendance: Evidence on the role of personality - St{\, Susi; Fahr, Rene (Applied Economics)

Arbeitskräftebedarf bei hoher Arbeitslosigkeit: ein ökonomisches Zuwanderungskonzept für Deutschland - Zimmermann, Klaus F; Bauer, Thomas K; Bonin, Holger; Fahr, Rene; Hinte, Holger

The impact of risk perception and risk attitudes on corrupt behavior: Evidence from a petty corruption experiment - Mir Djawadi, Behnud; Fahr, Rene

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.